Progression Rate from the Indeterminate Form to the Cardiac Form in Patients with Chronic Chagas Disease: Twenty-Two-Year Follow-Up in a Brazilian Urban Cohort - Hasslocher-Moreno, Alejandro Marcel (Trop Med Infect Dis, 2020)
Most patients with chronic Chagas disease (CD) present the indeterminate form and are at risk to develop the cardiac form. However, the actual rate of progression to the cardiac form is still unknown. Methods: In total, 550 patients with the indeterminate CD form were followed by means of annual electrocardiogram at our outpatient clinic. The studied endpoint was progression to cardiac form defined by the appearance of electrocardiographic changes typical of CD. The progression rate was calculated as the cumulative progression rate and the incidence progression rate per 100 patient years. Results: Thirty-seven patients progressed to the CD cardiac form within a mean of 73 ± 48 months of follow-up, which resulted in a 6.9% cumulative progression rate and incidence rate of 1.48 cases/100 patient years. Patients who progressed were older (mean age 47.8 ± 12.2 years), had a higher prevalence of associated heart diseases (p < 0.0001), positive xenodiagnosis (p = 0.007), and were born in the most endemic Brazilian states (p = 0.018). Previous co-morbidities remained the only variable associated with CD progression after multivariate Cox proportional hazards regression analysis (p = 0.002). Conclusion: The progression rate to chronic CD cardiac form is low and inferior to rates previously reported in other studies.